Plasma methods for toxic wastes processing (Physical Sciences and Technology, 2018)
Pollution of the environment with production waste is one of the most acute problems in the industrializedcountries. Many of the accumulated waste have the properties of toxicity, mutagenicity, carcinogenicity, firehazard and can affect both the health of the population in the regions where they are stored, and lead to theemergence of global environmental emergencies. Traditional technologies for the destruction of toxic waste invarious thermal installations are characterized by a relatively low process temperature. In the productremaining after processing, a significant quantity of primary and secondary pollutants formed in the process ofprocessing may be present in concentrations above the maximum permissible levels. The development of newmethods for the processing and destruction of toxic waste is one of the most urgent scientific and technicalproblems, the practical importance of which is undeniable. The use of thermal plasma for the destruction oftoxic wastes makes it possible to increase the minimum combustion / pyrolysis temperature in the reaction zoneof the reactor to 2000 K and above, thereby eliminating the course in the gas phase of the reaction with theformation of highly toxic compounds: phosgene, dioxins, polyhalogenated biphenyls and furans. Experimentalstudy of thermal neutralization of some toxic chlorine and bromine industrial wastes, as well as of pesticideswith an expired term of validity was carried out in the three-jet plasma reactor. Different physical-chemicalmethods were used for analysis of products of waste processing. It was shown that plasma technology provideseffective processing of toxic wastes.